Breaking the technical barrier of microvascular anastomosis with high-speed videography: A prospective cohort study. (February 2022) - Bao, Bingbo; Gao, Tao; Li, Xingwei; Wei, Haifeng; Lin, Junqing; Sun, Yi; Shen, Junjie; Zhu, Hongyi; Zheng, Xianyou
Abstract: Background: Microsurgical anastomosis is technically difficult especially for less-experienced surgeons. Traditionally, surgeons in training could only accomplish these surgeries under intensive guiding and supervision from senior surgeons. This study presents and characterises a new method for microsurgical trainees to objectively evaluating the quality of vascular anastomosis intraoperatively. Materials and methods: We conducted a prospective study to determine the utility of patency test of vascular anastomosis with assistance of high-speed video recording (PTHVR) to evaluate the quality of vascular anastomosis during microsurgery. To determine whether the use of PTHVR outperformed traditional supervision from senior surgeons (historical control), we compared the outcomes of microsurgeries including free flap transfer and replantation between the two groups. Results: A total of 211 patients were enrolled, of which 98 underwent surgery under traditional supervision and 113 underwent surgery with PTHVR. Of the 211 patients, 102 underwent digit replantation (48%), 22 underwent limb replantation (10%), and 87 underwent free flap transfer (42%). There was no statistical difference between the two groups in age, gender, BMI, pre-existing comorbidities, smoking status, alcohol consumption, and duration of surgery. Use of PTHVR as an intraoperative guide significantly decreased the rate of re-exploration surgeries (PTHVR, 8.0% [9/113]; control, 23.5% [23/98]; P = 0.002) and replantation/free flap failures (PTHVR, 8.8% [10/113]; control, 19.4% [19/98]; P = 0.029) compared with historical control under traditional supervision. Conclusions: PTHVR is a useful tool for improving the success rate of microsurgery for less-experienced surgeons when compared with traditional supervision mode. Highlights: The quality of vascular anastomosis lacks accurate and objective evaluation indexes. PTHVR is a useful tool for improving the success rate of microsurgery for less-experienced surgeons. PTHVR can help less-experienced surgeons quickly master high quality vascular anastomosis.